Hereditary Leiomyomatosis and Renal Cell Cancer: Recent Insights Into Mechanisms and Systemic Treatment - Zhang, Congwang; Li, Lijun; Zhang, Yipeng; Zeng, Changchun (Frontiers in Oncology, 2021)
Hereditary leiomyomatosis and renal cell carcinoma (HLRCC) is a rare autosomal dominant hereditary cancer syndrome characterized by a predisposition to cutaneous leiomyomas, uterine leiomyomas, and renal cell carcinoma (RCC). It is known to be caused by germline mutations of the fumarate hydratase (FH) gene, which encodes an enzyme component of the citric acid cycle and catalyzes the conversion of fumarate to L-malate. Currently, there is no standardized treatment for HLRCC, which may be due in part to a lack of understanding of the underlying mechanisms. Here, the underlying molecular mechanisms by which the inactivation of FH causes HLRCC are discussed. Additionally, potential therapeutic pharmacological strategies are also summarized to provide new perspectives for the prevention and treatment of HLRCC.